Harvesting biohydrogen from industrial wastewater: Production potential, pilot-scale bioreactors, commercialization status, techno-economics, and policy analysis. (15th March 2022) - Qyyum, Muhammad Abdul; Ismail, Sherif; Ni, Shou-Qing; Ihsanullah, Ihsanullah; Ahmad, Rizwan; Khan, Amin; Tawfik, Ahmed; Nizami, Abdul-Sattar; Lee, Moonyong
Abstract: Herein, recent reports on hydrogen production from wastewater were comprehensively evaluated. There are numerous methods of biohydrogen production from various types of wastewater. Fermentation is one of the most promising methods of biohydrogen production from industrial wastewater owing to its ease of operation and rapid hydrogen production. The sequential dark/photo fermentation approach generated a maximum hydrogen yield (HY) of 7.1 mol H2 /mol glucose with an estimated hydrogen production cost of 2.57 US $/kg and 2.83 US $/kg for dark and photo-fermentation, respectively. Pre-existing studies demonstrated that the successful implementation of pilot-scale fermentation bioreactors with a maximum hydrogen production rate (HPR) of 17 m 3 /m 3 ·d, but HPR is negatively correlated with reactor volume; more pilot-scale studies using high-strength wastewater for optimum performance are needed. The current implementation and commercialization challenges during hydrogen production were also highlighted in this review. Furthermore, a literature survey revealed research gaps associated with optimum conditions for maximized biohydrogen yield. Numerous review studies in literature focus on biohydrogen potential from solid biowaste; nevertheless, a comprehensive review on biohydrogen from wastewater is still needed. The recommendations of this review are designed to facilitate researchers and policymakers in achieving sustainable development goals (SDGs), including clean water and sanitation (SDG 6), renewable energy (SDG 7), sustainable communities (SDG 11), and climate action (SDG 13). Graphical abstract: Image 1 Highlights: Hydrogen (H2 ) is a sustainable energy source with near-zero emissions. Biohydrogen from industrial wastewater via fermentation is a promising approach. Optimum process parameters can contribute towards maximum hydrogen yield. Extensive pilot-scale studies need to be conducted using high-strength wastewater. Techno-economical assessment confirms the viability of H2 production.